2009
DOI: 10.1590/s1678-77572009000500027
|View full text |Cite
|
Sign up to set email alerts
|

Wear promoted in the apical third of simulated canals after instrumentation with protaper universal system

Abstract: Objective:This study evaluated the wear in the apical third of simulate canals after preparation with ProTaper Universal Rotary System.Material and Methods:24 sets of instruments were used in 24 simulated canals in transparent epoxy resin blocks with degree of curvature of either 20°or 40°. The canals were photographed preoperatively and after preparation of the apical stop with ProTaper F3, F4 and F5 instruments. The initial and final images were exported to Adobe Photoshop® software and superimposed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…However, the other bacteria tested were resistant. This result was in agreement with a previous study by (Melo et al, 2004), in which tricresol formalin's bactericidal actions were observed only against P. aeruginosa, and with a study by Silva et al (2006), in which tricresol formalin did not inhibit the growth of E. faecalis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the other bacteria tested were resistant. This result was in agreement with a previous study by (Melo et al, 2004), in which tricresol formalin's bactericidal actions were observed only against P. aeruginosa, and with a study by Silva et al (2006), in which tricresol formalin did not inhibit the growth of E. faecalis.…”
Section: Discussionsupporting
confidence: 93%
“…To test the antimicrobial properties of plants and chemicals, testing was performed using agar diffusion, as advocated by Bauer et al (1966) which is a reliable, inexpensive, reproducible and simple method that is widely used in microbiological research (Ohara et al, 1993;Estrela et al, 2000;Gomes et al, 2002;Drumond et al, 2004;Silva et al, 2006;Costa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, acrylic resin blocks allow the observation of the preparation in three dimensions along the whole canal length and a direct comparison of the shaping ability of different instruments 14 . In addition, they provide standardized length, diameter and angle of curvature of the simulated root canals 9 , 23 . From a statistical point of view, the standard deviation might increase whenever a range of curvatures is used, as opposed to the use of standardized acrylic resin blocks where this problem is minimized 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the final instrumentation size, the risk of transportation always increases in curved canals with an increase of file size 23 . Schafer and Vlassis 21 (2004) stated that ProTaper may induce apical transportation towards the outer aspect of the root canal especially because of the progressive tapers along the cutting surface of these instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies 18,19 also performed the same analysis by overlapping images and measuring deviations with the aid of Adobe Photoshop TM . However, this method of analysis has some limitations regarding measurement taking, as it conducts two-dimensional measurement taking of a tridimensional structure.…”
Section: Resultsmentioning
confidence: 99%